Pengaruh Aktivasi Arang Aktif dari Tongkol Jagung dan Tempurung Kelapa Terhadap Luas Permukaan dan Daya Jerap Iodin - Lela Mukmilah Yuningsih; Dikdik Mulyadi; A Jaka Kurnia (Jurnal Kimia Valensi, 2016)
The activated charcoal can be produced from various raw material which contains carbon such as corn cobs and coconut shell. Generally, activated charcoal made through activation process with added chemical materials. The kind of activator will give different influence on surface area or pores volume of the result activated charcoal. In this study, will be made activated charcoal from corn cobs and activated by physical and chemical with KOH activator. Carbonation process is performed at 800oC for 2 hours and followed by chemical activation process by KOH with mass ratio water: charcoal: KOH is 1:1:4, then activated by physical at 600oC for 4 hours. Conducted test on sample contain iodine adsorption and SEM. As a result, iodine adsorption of activated charcoal indicated at KOH 20%. the best adsorption of coconut shell activated charcoal is 1240.233 mg/g with surface area 2352.851 m2/g, while corn cobs activated charcoal is 1133.757 mg/g with surface area 2150.866 m2/g. Morphology of activated charcoal with KOH 20% have pore structure with high 22.63 µm and wide 26.41 µm, the resulting pore size included into macropores structure. Keywords: Activated charcoal, carbonation, activation, adsorption, surface area. DOI: http://dx.doi.org/10.15408/jkv.v2i1.3091